Agricultura familiar no estado de Santa Catarina: avaliação dos impactos ambientais e de trabalho dos produtores de morangos - Silva, Aline Santiago de Oliveira da (2019)
Brazilian production covers at least seven Brazilian states, with emphasis on Minas Gerais, São Paulo, Rio Grande do Sul, Espírito Santo, Santa Catarina, Paraná, and the Federal District. The municipalities Catarinenses, Içara and Rancho Queimado stands out in the production of the Strawberries. This research was exploratory-descriptive, using bibliographical and field research, through the case study producers from the municipalities of Içara and Rancho Queimado. Two methodological tools were combined: the Leopold matrix for the application of environmental impact studies composed of indicators versus impact factors, which allowed assigning degree and impactimportance values for each item analyzed. And for the survey of the physical demands of the tasks imposed on workers in the production of strawberries, the scale of corporal discomfort, which aims to raise the producers' grievances during their working day and the OWAS method, which seeks to define the risks of illness in relation to to the postures adopted during the work activities and the cognitive requirements were obtained through in loco observations. This dissertation presented an innovative character, as it provided the combination of two theoretical-methodological environmental impacts and Ergonomics. The two approaches combined made it possible to elaborate the recommendations, which pointed out alternatives to the generated waste, such as reverse logistics, impacts on natural resources, proposing the insertion of renewable energies, reuse of water, and measures were indicated for questions concerning the conditions of work, health and safety of producers, examples that converge towards the expanded concept of sustainability, that is, taking into account the three pillars: social, environmental and economic